The Effect Of Industry Type, Government Pressure, And Company Size To Disclosure Of Sustainability Report - Tri Siwi Nugrahani; Khoirinida Isnaini Atiqoh; Imanda Firmantyas Putri Pertiwi (Journal of Business and Management Review, 2022)
This study examines the effect of industry type, government pressure, and company size on the disclosure of sustainability reports in 41 companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sampling method is purposive sampling. Total observations of 164 companies. This study uses multiple linear regression analysis techniques. The results of the study prove that the type of industry and government pressure have a significant positive effect on the disclosure of sustainability reports. However, the size of the company does not affect the disclosure of the sustainability report.